Transcriptomic analysis of bone transport reveals different functions between both ends - Wang, Maochun; Zhang, Jiao; Qiao, Chongxu; Yan, Shunchao; Gao, Weicheng; Wu, Guoping (Frontiers in Physiology, 2025)
BackgroundBone fractures are common in both young and elderly populations, and bone transport surgery is a critical orthopedic procedure for patients with severe fractures, bone defects, and non-unions. However, the specific molecular mechanisms driving bone healing during bone transport, particularly the roles of compressive and tensile ends, remain poorly understood.MethodsWe utilized transcriptomic analysis of bone tissues from a rat bone transport model to explore differential gene expression patterns associated with compressive and tensile ends.Results233 differentially expressed genes (DEGs) were identified in the tensile end (TE) group and 317 DEGs in the compressive end (CE) group, compared to the control group. These DEGs were enriched in distinct biological processes. The TE group was primarily associated with bone healing processes such as ossification, extracellular matrix organization, and bone development. Key genes in the TE group, including Bglap, Acan, Mmp13, and Runx2, were upregulated, highlighting their roles in osteogenesis. In contrast, the CE group showed enrichment in processes related to myogenesis, such as muscle system processes and skeletal muscle tissue development. Core genes in the CE group, including Chrna1, Chrnd, Myod1, and Rps6kb1, were upregulated, indicating a focus on myogenesis and its indirect impact on bone healing. Notably, 15 DEGs were shared between the TE and CE groups, with consistent expression trends, suggesting partially overlapping molecular mechanisms in bone healing under different mechanical ends.ConclusionThese findings provided insights into the distinct and shared molecular pathways involved in bone regeneration during bone transport and could inform targeted therapeutic strategies to enhance bone healing.